2013
DOI: 10.1007/s11136-012-0343-z
|View full text |Cite
|
Sign up to set email alerts
|

Condition-specific quality of life questionnaires for caregivers of children with pediatric conditions: a systematic review

Abstract: The increasing number of questionnaires developed over time shows improved recognition of the importance of caregiver QoL. There is a paucity of QoL questionnaires for caregivers of otherwise healthy children suffering from physical injuries and acute conditions associated with significant caregiver burden. Cultural validation of existing and new questionnaires in lower-income countries is necessary. Data collected by condition-specific questionnaires can assist clinicians and health economists in estimating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 70 publications
1
26
0
1
Order By: Relevance
“…According to our preliminary study, this scenario is confirmed in CD, although its prognosis is more benign than in other chronic diseases, such as arthritis, diabetes or cancer (32). The aforementioned results suggest that the caregivers' burden should be assessed at clinical onset, when some alarm symptoms, e.g., diarrhea, weight loss and abdominal pain, might be responsible for higher degree of distress.…”
Section: Resultssupporting
confidence: 55%
“…According to our preliminary study, this scenario is confirmed in CD, although its prognosis is more benign than in other chronic diseases, such as arthritis, diabetes or cancer (32). The aforementioned results suggest that the caregivers' burden should be assessed at clinical onset, when some alarm symptoms, e.g., diarrhea, weight loss and abdominal pain, might be responsible for higher degree of distress.…”
Section: Resultssupporting
confidence: 55%
“…Quality of life (QOL) is regarded as an important marker of the impact of health conditions on patients and their families and is consequently a major outcome measure in research and clinical interventions of chronic disease (Chow, Morrow, Robbins, & Leask, 2013; Indinnimeo, et al, 2014). Identifying risk and protective correlates of QOL in asthma populations is further significant since caregiver QOL is proposed to influence health self-management behaviors such as treatment adherence and decisions about seeking healthcare services (Osman & Silverman, 1996), which may have a significant impact on asthma control.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, a child's illness is likely to affect a parent's quality of life (QoL). 19 Quality of life as defined by the World Health Organization (WHO) is ''an individual's perception of their position in life in the context of the culture and value systems in which they live, and in relation to their goals, expectations, standards, and concerns.'' 20 Given this, it is important to know how satisfied or bothered people are by important aspects of life.…”
mentioning
confidence: 99%